2009
DOI: 10.1002/art.24341
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective seven‐year analysis of the use of B cell depletion therapy in systemic lupus erythematosus at university college london hospital: The first fifty patients

Abstract: Objective. To describe the 6-month clinical outcome and the long-term safety profile of B cell depletion therapy (BCDT) in 50 patients with active systemic lupus erythematosus (SLE), who were nonresponsive or poorly responsive to conventional immunosuppression. Methods. All except 4 of 50 patients with active SLE received 1 gm of rituximab, 750 mg of cyclophosphamide, and 100 -250 mg of methylprednisolone, administered on 2 occasions 2 weeks apart, to achieve B cell depletion. Clinical outcome was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
149
1
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(166 citation statements)
references
References 66 publications
6
149
1
10
Order By: Relevance
“…For instance, in Gunnarsson's experience in 7 cyclophosphamide-resistant female patients treated with a combination of RTX and cyclophosphamide [34], the SLEDAI score and anti-dsDNA significantly dropped, while on repeat renal biopsy, improvement in the histopathological class of nephritis with a decrease in the renal activity index occurred in the majority of patients. Similarly promising results were obtained in Lu's large series in refractory patients [33]. More recently, in an uncontrolled, single centre study involving 8 SLE patients with severe multiorgan involvement who received an intensive treatment course of 4 plus 2 infusions of RTX (375 mg/m2 on days # 2, 8, 15 and 22 with 2 more doses administered 1 and 2 months following the last weekly infusion), combined with two pulses of 750 mg cyclophosphamide (days # 4 and 17) and three pulses of 15 mg/kg methylprednisolone (days #1, 4 and 8) followed by oral prednisone, 50 mg for 2 weeks rapidly tapered until 5 mg in 2 months, proteinuria remarkably improved in the nephritic patients, and the SLEDAI score dropped from 17.3 (12-27) before therapy to 3.1 (1-5) after RTX [36].…”
Section: Lupus Nephritissupporting
confidence: 65%
See 1 more Smart Citation
“…For instance, in Gunnarsson's experience in 7 cyclophosphamide-resistant female patients treated with a combination of RTX and cyclophosphamide [34], the SLEDAI score and anti-dsDNA significantly dropped, while on repeat renal biopsy, improvement in the histopathological class of nephritis with a decrease in the renal activity index occurred in the majority of patients. Similarly promising results were obtained in Lu's large series in refractory patients [33]. More recently, in an uncontrolled, single centre study involving 8 SLE patients with severe multiorgan involvement who received an intensive treatment course of 4 plus 2 infusions of RTX (375 mg/m2 on days # 2, 8, 15 and 22 with 2 more doses administered 1 and 2 months following the last weekly infusion), combined with two pulses of 750 mg cyclophosphamide (days # 4 and 17) and three pulses of 15 mg/kg methylprednisolone (days #1, 4 and 8) followed by oral prednisone, 50 mg for 2 weeks rapidly tapered until 5 mg in 2 months, proteinuria remarkably improved in the nephritic patients, and the SLEDAI score dropped from 17.3 (12-27) before therapy to 3.1 (1-5) after RTX [36].…”
Section: Lupus Nephritissupporting
confidence: 65%
“…The response rate in the RTX arm was 57% versus 46% in the standard therapy arm and this was not statistically significant, though there was a trend toward benefit in the African-American and Hispanic subset of patients [32]. Background treatment, concomitant therapies and ethnic factors have been emphasized as relevant factors in explaining the different outcomes of patients recruited in controlled and uncontrolled studies [33], [34] and [35]. Open-label studies focused on patients who were either refractory or intolerant to standard immunosuppressants and who were unlikely to be included in randomized controlled studies.…”
Section: Lupus Nephritismentioning
confidence: 99%
“…In an article recently published in Arthritis Care & Research, Lu et al presented the largest series of patients with systemic lupus erythematosus (SLE) treated with rituximab reported from a single center (1). Two characteristics of this study deserve mention.…”
Section: To the Editorsmentioning
confidence: 89%
“…Regarding ethnic factors, the 2 RCTs included American patients, predominantly from the US and Canada, but also from Mexico, Brazil, and Argentina. However, the majority of patients from recent uncontrolled studies were European (1,6,7,9,11,12). This ethnicity is important because some studies have suggested a variable therapeutic response to the main immunosuppressive agents in different ethnic groups (13).…”
Section: To the Editorsmentioning
confidence: 99%
“…Rituximab, an anti-CD20 monoclonal antibody that depletes B cells, is useful in inducing remissions in some patients with severe lupus nephritis, including those who have failed cyclophosphamide or MMF therapy. 29,30 However, recent data from two randomized controlled trials in which rituximab or placebo were added to standard immunosuppressive regimens failed to show a benefit for rituximab in this setting. The Exploratory Phase II/III SLE Evaluation of Rituximab trial tested the efficacy and safety of rit- uximab versus placebo in 257 patients with moderately-to-severely active extrarenal SLE but without lupus nephritis.…”
Section: Conservative Nonimmunomodulatory Therapy Is Appropriate Formentioning
confidence: 99%